(untitled) (Torani Journal of Fisheries and Marine Science, 2017)
Sandeq is a kind of marine transportation , since long has been operated by Mandar seaman and fishers along the coastal water area, as well as for fishing in Sulawesi Barat . This research was carried out to study the feasibility of utilizing the Sandeq boat in marine ecotourism in Pasir Putih Island of the Polewali Mandar Regency. SWOT Analisys has been applied to reveal the level of support of stakeholders regarding this idea, and the strategies to be carried out in developing this specific ecotourism. The analysis shows that the internal and external factors are strongly support the program with a strong and aggressive manner and having a positif opportunity. A scenario on commercially operated ecotourism was designed and financially analyzed for 5 years period of operation: (1) Net present value of Rp 705.121.922,-, (2) Internal rate of returnof 100,99 %, and B/C ratio range from 1.7 at 3nd year to 3.7 at the 5th year. Those values showed that the project is financially feasible. Three alternatives routes of marine ecotourism werw iidentified: (1) Ballanipa Village to Karamasang Island, (2)From Balanipa Village to Battoa Island, (3) From Tonyaman Village to Karamasang Island and Pasir Putih. Key words : Sandeq boat, ecotourism, Pasir Putih Island, Polewali mandar Regency, Swot Analysis, Financial analysis.